Creativity, education or what? On the measurement of regional human capital - Eckhardt Bode; Lucia Perez Villar (Kiel Institute for the World Economy (IfW), 2014)
This paper substantiates the debate following Richard Florida's suggestion to measure regional human capital by creative occupations rather than education. Consistent with Florida's notion of creativity, it suggests a microfoundation that relates creativity to workers' cognitive and noncognitive skills. It shows that this microfoundation is similar to that of human capital in recent labor economics, which has facilitated important new insights. It also shows that Florida's measure is too crude to make a difference. Nonethe-less, it is time to rethink regional human capital. Occupations may help project workers' cognitive and noncognitive skills from the micro to the regional level.
Keywords: I21; I25; J24; R12; R23; 330; Human Capital; Education; Creativity; Cognitive Skills; Noncognitive Skills; Occupation; Regional Wages; Regional Growth